2021
DOI: 10.12998/wjcc.v9.i26.7923
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of an inborn error of bile acid synthesis type 4: A case report

Abstract: BACKGROUND Inborn error of bile acid synthesis type 4 is a peroxisomal disease with impaired bile acid synthesis caused by a-methylacyl-CoA racemase ( AMACR ) gene mutation. The disease is usually found in children with mild to severe liver disease, cholestasis and poor fat-soluble vitamin absorption. At present, there is no report of inborn errors of bile acid synthesis type 4 in adults with liver disease and poor fat-soluble vitamin absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Interestingly, Wang et al reported a 71-year-old male with jaundice and the absence of seizures, which contradicts the general ideology that neurological symptoms are exclusive to adult patients with AMACR deficiency [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, Wang et al reported a 71-year-old male with jaundice and the absence of seizures, which contradicts the general ideology that neurological symptoms are exclusive to adult patients with AMACR deficiency [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a case by Setchell et al, chronic supplementation of cholic acid reverted liver enzymes back to normal and prevented future progression of symptoms [ 11 ]. Since malabsorption of these vitamins is a feature of this disease, supplementation of the deficient fat-soluble vitamins is a crucial pillar in the treatment strategy [ 2 , 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BAs are a general term for a group of bile alkanoic acids that are metabolized from cholesterol in the hepatocytes and are the main components of bile [ 13 , 14 ]. The type and structure of BAs vary depending on the animal species, but in pigs, they are mainly α-deoxycholic acid, bilirubin, and goose deoxycholic acid.…”
Section: Discussionmentioning
confidence: 99%